Assessing secondary students’ awareness of STEM education: Preliminary findings - Kamsia Budin; Siti Rahayu Mohd. Hashim; Hasrizal Mohamad; Noriati Budin; Rapidaya Budin; Masdia Budin; Fauziah Sulaiman (Springer Verlag, 2025)
STEM (Science, Technology, Engineering, and Mathematics) education is crucial in fostering innovation and economic development. Despite various government initiatives in Malaysia, students’ interest and participation in STEM fields remain a concern, particularly in rural areas. This paper assesses secondary students’ awareness toward STEM education, analyzing the factors influencing their engagement, including interest in Science, Mathematics, Technology & Engineering, and English proficiency. The study conducted research designed a cross-sectional adapted survey on STEM awareness among 496 secondary students in Tawau, Sabah, which is considered a rural area. The findings reveal that Science awareness has the highest impact on STEM engagement, followed by Technology & Engineering, Mathematics, and English proficiency. Mathematics anxiety is a significant barrier to STEM participation, affecting students’ confidence in pursuing STEM-related careers. The study also high- lights geographical and socioeconomic disparities, with rural students havingAQ2 lower exposure to quality STEM resources compared to their urban counterparts. To enhance STEM awareness and participation, targeted interventions, such as hands-on STEM learning, improved Mathematics instruction, career guidance, and equitable access to resources, are necessary. These insights contribute to shaping educational policies and strategies to bridge the STEM engagement gap and prepare students for future STEM careers.